Extended boiling of peanut progressively reduces IgE allergenicity while retaining T cell reactivity. Issue 7 (12th May 2016) - Tao, B.; Bernardo, K.; Eldi, P.; Chegeni, N.; Wiese, M.; Colella, A.; Kral, A.; Hayball, J.; Smith, W.; Forsyth, K.; Chataway, T.
Summary: Background: Current peanut oral immunotherapy is hampered by frequent adverse events. It has been shown that boiling can reduce peanut allergenicity. Hypoallergenic peanut products have the potential to reduce treatment‐related reactions during desensitization. Objective: To show that extended boiling (for up to 12 h) can progressively reduce peanut allergenicity while retaining T cell reactivity. Methods: Raw peanuts were boiled for half, 1, 2, 4 and 12 h in deionized water. After dehydration, boiled and raw peanuts were ground, defatted and soluble proteins extracted in PBS and cooking water (leachate) retained. SDS‐PAGE, Western blot, inhibition ELISA, mass spectrometry and skin prick test were used to characterize changes to peanut allergens and human IgE reactivity. T cell responses to raw and boiled peanut extracts were determined by proliferation of CD4+/CD25+/CD134+ T cells in peanut‐allergic and non‐allergic individuals. Results: Extended boiling progressively reduced peanut allergenicity through a combination of leaching of allergens into cooking water, fragmentation of allergens and denaturation of conformational epitopes. Two‐hour boiling led to an eightfold reduction in IgE binding capacity of boiled peanuts as determined by inhibition ELISA, while 12‐h boiling led to a 19‐fold reduction. Mass spectrometry revealed an increasing number of unique allergen peptides with longer boiling times. Raw, 2‐ and 12‐h boiled peanut extracts were equivalent in their ability to stimulate T cell activation and proliferation. Conclusion and Clinical Relevance: Progressive reduction in peanut allergenicity with extended boiling does not affect T cell reactivity. Boiled peanuts may be a candidate for oral immunotherapy.